The Influence Of Content Marketing, Online Customer Reviews And Online Customer Ratings On Purchasing Decisions At Tiktok Shop - Pasha, Himalaya (Al-Adzkiya Publisher, 2024)
The aim of this research is to determine and analyze the influence of content marketing on purchase decisions, to determine and analyze the influence of online customer reviews on purchase decisions, to determine and analyze the influence of online customer ratings on purchase decisions, and to determine and analyze the influence of content marketing, online customer reviews, and online customer ratings on purchase decisions in TikTok Shop among students of the Faculty of Economics and Business at the University of Muhammadiyah North Sumatra. The approach used in this research is an associative approach. The population in this study consists of all active undergraduate students of the Faculty of Economics and Business at UMSU who enrolled from 2019 to 2022, totaling 4,432 individuals, and the sample size used in this study is 75 individuals, determined using the Slovin formula. Data collection in this research is done through questionnaires. Data analysis techniques in this study include Multiple Linear Regression, Classical Assumption Tests, t-tests, and F-tests, as well as the Coefficient of Determination. Data processing in this study is performed using SPSS software (version 24.00). Partially, content marketing has a significant influence on purchase decisions. Partially, online customer reviews have a significant influence on purchase decisions. Partially, online customer ratings have a significant influence on purchase decisions. Simultaneously, content marketing, online customer reviews, and online customer ratings have a significant influence on purchase decisions in TikTok Shop among students of the Faculty of Economics and Business at the University of Muhammadiyah North Sumatra.